Soluble TNF receptors predict acute kidney injury and mortality in critically ill COVID-19 patients: A prospective observational study. (January 2022) - Sancho Ferrando, Elena; Hanslin, Katja; Hultström, Michael; Larsson, Anders; Frithiof, Robert; Lipcsey, Miklos; ,
Highlights: SARS-CoV-2 infection has wide range of clinical manifestations and illness severity. Soluble TNF receptors 1 and 2 (sTNFR) play a key role during COVID infection. sTNFR identify COVID-19 patients at risk of acute kidney injury (AKI) and death. Abstract: Background: Although pneumonia is the hallmark of coronavirus disease 2019 (COVID-19), multiple organ failure may develop in severe disease. TNFα receptors in their soluble form (sTNFR) are involved in the immune cascade in other systemic inflammatory processes such as septic shock, and could mediate the inflammatory activation of distant organs. The aim of this study is to analyse plasma levels of sTNFR 1 and 2 in association with organ failure and outcome in critically ill patients with COVID-19. Methods: After informed consent, we included 122 adult patients with PCR-confirmed COVID-19 at ICU admission. Demographic data, illness severity scores, organ failure and survival at 30 days were collected. Plasma sTNFR 1 and 2 levels were quantified during the first days after ICU admission. Twenty-five healthy blood donors were used as control group. Results: Levels of sTNFR were higher in severe COVID-19 patients compared to controls (p < 0.001). Plasma levels of sTNFR were associated to illness severity scores (SAPS 3 and SOFA), inflammation biomarkers such as IL-6, ferritin and PCT as well as development of AKI during ICU stay. sTNFR 1 higher than 2.29 ng/mL and? sTNFR 2 higher than 11.7 ng/mL were identified as optimal cut-offs to discriminate survivors and non-survivors 30 days after ICU admission and had an area under the curve in receiver operating characteristic curve of 0.75 and 0.67 respectively. Conclusion: Plasma levels of sTNFR 1 and 2 were higher in COVID-19 patients compared to controls and were strongly associated with other inflammatory biomarkers, severity of illness and acute kidney injury development during ICU stay. In addition, sTNFR 1 was an independent predictor of 30-day mortality after adjustment for age and respiratory failure.